Analysis of the personality traits of urban tourism brand on visiting intention through perceived consistency (studied in Tehran) - Yazdan Shirimohamadi; Ali Shamaei; Seyyed Eshagh Jalalian; Farzaneh Rafiee (تحقیقات کاربردی علوم جغرافیایی)
It is important to examine the effect of the tourist personality on the choice of tourist destination. In the meantime, using Hofstede's cultural model in analyzing the effect of tourist personality dimensions on the intention to visit through the perceived homogeneity variable greatly helps to understand this issue. In this research, the effects of femininity, masculinity, ambiguity, avoidance of individualism and collectivism on the intention to visit have been analyzed. This research is applied in terms of purpose and methodological in addition to descriptive and survey research. In this regard, 384 questionnaires were distributed among tourists from German, Japanese, French, Arab (Iraqi), Italian, Austrian, Chinese nationalities residing in five star hotels in Tehran. Structural equation index was used for data analysis. The results show that tourists prefer brands that match their perception of the destination brand. The findings of the study indicate that the personality dimensions of the tourist intent through the popularity of tourism destinations and the image of tourist destinations influence on the perceived homogeneity of the urban tourism brand and the masculinity of the tourism city brand; Perceived homogeneity of urban tourism brand is effective and femininity of tourism city brand does not affect perceived homogeneity of urban tourism brand. The results of this study indicate that Tehran has a masculine brand and people are selected to be masculine and to be collectivist and ambiguous. In fact, the results of the study showed that in selecting tourism markets for Tehran, one should look for tourism markets that are characteristic of the Hofstede model in terms of masculinity, ambiguity and collectivism, as well as the development of tourism spaces for women.